The Bed Nucleus of the Stria Terminalis Mediates Inter-individual Variations in Anxiety and Fear - Duvarci, Sevil (Society for Neuroscience, 2009)
While learning to fear stimuli that predict danger promotes survival, the inability to inhibit fear to inappropriate cues leads to a pernicious cycle of avoidance behaviors. Previous studies have revealed large inter-individual variations in fear responding with clinically anxious humans exhibiting a tendency to generalize learned fear to safe stimuli or situations. To shed light on the origin of these inter-individual variations, we subjected rats to a differential auditory fear conditioning paradigm in which one conditioned auditory stimulus (CS+) was paired to footshocks whereas a second (CS−) was not. We compared the behavior of rats that received pretraining excitotoxic lesions of the bed nucleus of the stria terminalis (BNST) to that of sham rats. Sham rats exhibit a continuum of anxious/fearful behaviors. At one end of the continuum were rats that displayed a poor ability to discriminate between the CS+ and CS−, high contextual freezing, and an anxiety-like trait in the elevated plus maze (EPM). At the other end were rats that display less fear generalization to the CS−, lower freezing to context, and a nonanxious trait in the EPM. Although BNST-lesioned rats acquired similarly high levels of conditioned fear to the CS+, they froze less than sham rats to the CS−. In fact, BNST-lesioned rats behaved like sham rats with high discriminative abilities in that they exhibited low contextual fear and a nonanxious phenotype in the EPM. Overall, this suggests that inter-individual variations in fear generalization and anxiety phenotype are determined by BNST influences on the amygdala and/or its targets.